(untitled) (Annals of Medical Research, 2022)
Aim: The histological stage is crucial for the management of the patients with chronic hepatitis C. Because of the invasiveness and some limitations of liver biopsy a lot of noninvasive tests are in search intensively to use instead of liver biopsy. In this study, we searched the relationship of neutrophil to lymphocyte ratio with the stage of inflammation and fibrosis in histology in patients with chronic hepatitis C. Materials and Methods: This study retrospectively investigated data of 62 patients with chronic hepatitis C and 40 healthy controls. Results: Mean neutrophil to lymphocyte ratio values in chronic hepatitis C and control groups were 1.86 (0.89-3.94) and 1.38 (0.73-2.93) respectively (p=0.001). In the chronic hepatitis C group there were 23 (%37) patients with advanced fibrosis (Ishak score>2) and 39 (%63) patients with mild fibrosis (Ishak score≤ 2). In patients with advanced fibrosis, mean neutrophil to lymphocyte ratio was high according to patients with mild fibrosis (2.10 (1.21-3.54) and 1.71(0.89-3.94) respectively, p=0.006). In receiver operating characteristic (ROC) curve analysis, cut off value for neutrophil to lymphocyte ratio in advanced fibrosis was 1.76 (sensitivity 86.9%, specificity 61.5%, NPV 88.9%, PPV 57.1%, AUC: 0.711). Conclusion: Neutrophil to lymphocyte ratio can predict fibrosis stage in chronic hepatitis C. But more studies are necessary to use neutrophil to lymphocyte ratio in clinical practice or how this parameter change with treatment.